Misi Gereja Era Post Modern - Robert William; Ferry Simanjuntak (Journal of Industrial Engineering & Management Research, 2022)
The symptoms caused by the postmodern current that characterize the dynamics of church ministry that exist in the Church today and produce results, namely the fading of true Christian truth. The purpose of this research is so that the Church has the understanding, understanding and knowledge to anticipate and teach it to all missionary congregations in the face of postmodern currents that have permeated various fields of life today. The method used in this research is a descriptive method, with the type of library research. Therefore, the Church that can anticipate the challenges of this postmodern era is the Church that reaps many souls in this era.